ChemInform Abstract: Fiber Based Structured Materials for Catalytic Applications. Issue 26 (1st July 2014) - Reichelt, Erik; Heddrich, Marc P.; Jahn, Matthias; Michaelis, Alexander
Abstract Review: 212 refs.